Experimental behavior of steel-beam to flat rectangular CFST column connections with small-sized external diaphragms. (November 2022) - Tong, Lewei; Huang, Junfeng; Wu, Honglei; Wang, Kaiyuan; Dong, Baiping
Abstract: This paper experimentally investigates the hysteretic behavior of beam-to-column connections between steel beams and flat rectangular concrete filled steel tubular (CFST) columns with small-sized external diaphragms to enable the implementation of the connections in steel structure residential buildings. The flat rectangular CFST columns are characterized by the width-to-depth ratio of the cross-section greater than 2.0. Five test specimens, including three corner connections and two interior connections in a frame structure, with 400×200 mm rectangular CFST column cross-section and various sizes of external diaphragms are designed for the investigation. During the tests, the specimens are subjected to constant axial loads on the columns and cyclic vertical loads at the beam ends that impose bending moments about the strong and weak axis of the columns. Failure modes including buckling in beam flanges, cracking at the welded connections between beam flanges and external diaphragms, and shear failure in panel zones are observed. The load-displacement hysteresis and strain distribution are obtained to evaluate the elastoplastic behavior of the connections. The moment resistance capacity, ductility, energy dissipation capacity, as well as stiffness and strength degeneration of the connections are respectively evaluated. The test results demonstrate that the connections have adequate hysteretic performance for earthquake resilient design of steel structure residential buildings. It is applicable to use small-sized external diaphragms beyond the limitation of existing design specifications for beam-to-column connections with flat rectangular CFST columns. Highlights: Small-sized external diaphragm is proposed for beam to flat CFST column connections. The behavior of the connections is experimentally studied. The failure modes of connections with various design configurations are revealed. The hysteretic performance and resistance of the connections are evaluated. The applicability of the connections for seismic resistant design is validated.